A new protection scheme for an SSSC in an MV network by using a varistor and thyristors - Bashar,E; Rogers,D; Wu,R; Ran,L; Jennings,M; Green,TC; Mawby,P (IEEE Transactions on Power Delivery, 2021)
To control power flow and manage fault level in meshed MV networks, back-to-back voltage source converters (B2B-VSCs) are being used. However, their high cost and relatively low efficiency are of concerns. Partially rated series compensators, such as SSSCs or UPFCs, are desired but come with the challenge of protecting the device during grid faults. Their potential of use has been limited in comparison with the fully rated back-to-back converters. This paper proposes a new system topology including thyristor crowbars and a varistor to protect the SSSC in an MV network and improve the reliability and flexibility of the network operation. Using the proposed method, the time required for isolating the series compensator from the grid is reduced from at least 20 ms, corresponding to the interruption time of conventional circuit breakers, down to 3 μs in the worst case in addition to the grid fault detection delay. The performance is evaluated by simulation. A small-scale single-phase prototype operating at 230 V/16 A is tested in order to demonstrate the concept.